(untitled) (Minerva, 2019)
Through this paper the author proposes a new assessment of the traditional hypothesis developed in the accounting of palatalization of labiovelars in Ancient Greek. In a typological framework some epigraphic data have been analysed and explained to try to account for two striking inconsistent treatments of labiovelars in several dialects, mainly in Aeolian. The unlike palatalization before mid front vowels and secondary, the greater palatalization in number of frecuency of labiovelars instead of pure velar in the same phonetic contexts.